Donor Blood Procurement, Safety, and Clinical Utilization: A Study of Blood Transfusion Services in a Tertiary Care Hospital in Nigeria. (17th March 2022) - Nnachi, Oluomachi Charity; Uzor, Charles; Umeokonkwo, Chukwuma David; Onwe, Emeka Ogah; Okoye, Augustine Ejike; Ewah, Richard Lawrence; Nwani, Favour Ogonna
Abstract : Background . Donated blood is an essential component of the management of many diseases, and hospital-based blood banks in Nigeria are saddled with the responsibility of provision of safe blood and coordination of its appropriate utilization for patient care. Objective . This study reviewed the extent to which the hospital blood transfusion service ensures adequate safe blood supply and utilization. Materials/Methods . This was a retrospective study of 2 years record of the blood bank service of Alex Ekwueme Federal University Teaching. Methods of donor blood procurement, transfusion transmissible infection status, the pattern of blood, and blood component usage across the hospital's clinical departments were evaluated. Statistical analysis was conducted using IBM SPSS, and data were presented as percentages. Fisher's tests were used to test significance, and p value <0.05 is significant. Results . The highest proportion of donors was male family replacement donors aged 26–35 years (3634 (39.68%)) while total voluntary donors were 315 (2.65%). Hepatitis B had the highest seroprevalence 267 (2.22%) among blood-borne diseases screened. National Blood Transfusion Service (NBTS) supplied only 3 (0.03%) of total blood units used. The accident and emergency department had the highest proportion of persons who utilized whole blood; 4568 (99.96%). Conclusion . The hospital blood bank relies heavily on family replacement donors with little or no assistance from the National Blood Transfusion Service. Family replacement donors have the highest risk of TTIs, and hepatitis B infection has the highest prevalence. The high cost of blood component therapy increases the need for whole blood.